Pemertahanan Bahasa Bali di Kabupaten Lombok Barat - Desak Made Yoniartini; Mahsun; Burhannudin (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
The threat of extinction of regional languages in Indonesia is increasingly evident, Balinese is one of the regional languages experiencing this threat, the massive use of Indonesian and other languages is alleged to be the cause. This article discusses the maintenance of Balinese language in the Regency of West Lombok, an island next to Bali, where the Balinese language is spoken by a minority of people. Data were collected from primary and secondary sources including by speaking and listening (cakap dan simak) techniques. Data were analyzed by using qualitative methods and presented by narrative methods. The results of the study show that the Balinese language in West Lombok Regency is surviving, this is seen from various aspects, namely, Balinese ethnic children master and use the Balinese language well, the massive use of Balinese in various areas of life, and concrete steps taken to make efforts to maintain the language to the fullest.